2008
DOI: 10.1097/cji.0b013e318183af0b
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With Analog Peptide in Combination With CpG and Montanide Expands Tumor Antigen-specific CD8+ T Cells in Melanoma Patients

Abstract: Analogue peptides represent a promising tool to further optimize peptide-based vaccines in promoting the expansion of tumor antigen-specific CTLs. Here, we report the results of a pilot trial designed to study the immunogenicity of the analogue peptide NY-ESO-1 157-165V in combination with CpG 7909/PF3512676 and Montanide ISA 720 in patients with stage III/IV NY-ESO-1-expressing melanoma. Eight Patients were immunized either with Montanide and CpG (arm 1, three patients), Montanide and peptide NY-ESO-1 157-165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 29 publications
3
68
0
Order By: Relevance
“…Similar modifications have led to peptide analogues which are effective at inducing immune responses against a range of tumor types including leukemia and solid tumors [54, [57][58][59]94,95](reviewed in [96]). Despite inherent problems in demonstrating the ability of modified peptides to recognize and kill tumor cells, some heteroclitic epitopes have shown promise in phase I clinical trials [18,71,97].…”
Section: Discussionmentioning
confidence: 99%
“…Similar modifications have led to peptide analogues which are effective at inducing immune responses against a range of tumor types including leukemia and solid tumors [54, [57][58][59]94,95](reviewed in [96]). Despite inherent problems in demonstrating the ability of modified peptides to recognize and kill tumor cells, some heteroclitic epitopes have shown promise in phase I clinical trials [18,71,97].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that CpG-A or various DNAs needed to be retained for long periods in the endosomes of pDCs for sufficient activation of TLR9 signaling (25,26). Recently, CpG-ODNs have shown promising results as vaccine adjuvants for cancer immunotherapy due to their ability to induce potent Th1-type immune responses and anti-tumor responses (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Patient F-9 even exhibited an ex vivo detectable T-cell response against NY-ESO-1 p157-165. Direct ex vivo antigen-specific T cells are rarely detected, but were found in several previously published studies either with NY-ESO-1 p157-165 peptide or Melan-A ELA-GIGILTV analog peptide when the vaccines were combined with Montanide and CpG (15,41,42). These studies indicate the important role of CpG as an adjuvant in peptide-based and recombinant protein vaccines.…”
Section: Discussionmentioning
confidence: 81%